Servant Leadership Dalam Manajemen Pendidikan: Konsep, Praktik, Dan Implikasinya Terhadap Kinerja Dan Kesejahteraan Pendidik - Elya Indah Rahmawati; Putri Ellen Gracia Risamasu; Winda Fashihah; Achmad Supriyanto (Varied Knowledge Journal, 2025)
This study aims to examine the concept, practice, and implications of servant leadership within the context of educational management, as well as its impact on teachers’ performance and well-being. Using a qualitative approach with a library research method, this study explores theoretical frameworks and previous empirical findings related to servant leadership in educational institutions. The results indicate that servant leadership emphasizes service, empathy, empowerment, and personal growth as the core values of leadership. In educational settings, the implementation of servant leadership enhances teacher performance by fostering motivation, trust, and a positive organizational climate. Furthermore, this leadership style contributes to teachers’ psychological and professional well-being through emotional support, recognition, and empowerment of job resources. Theoretically, servant leadership acts as a catalyst linking value-based leadership with sustainable educational outcomes. Therefore, it is considered a relevant model for developing human-centered, collaborative, and service-oriented educational institutions.